Novel Biomarkers in the Early Detection of Chronic Kidney Disease: Current Evidence and Future Directions - Iftikhar, Arishba; Ishtiaq, Qasim; Uzair, Muhammad; Nazir, Quratul Ain; Ch, Akif Saeed; Khan, Zafar Ahmad (Indus Journal of Bioscience Research, 2025)
Chronic kidney disease (CKD) affects over 850 million individuals worldwide, with conventional markers failing to detect early renal damage until significant nephron loss occurs. This review synthesizes current evidence on emerging biomarkers—including proteomic signatures (e.g., CKD273 panel), metabolomics profiles, circulating microRNAs, APOL1 genetic variants, cell-free DNA methylation patterns, and urinary exospores that enable earlier detection of CKD. We examine multi-marker panels integrated with machine-learning algorithms, achieving high sensitivity and specificity in prospective cohorts, and assess point-of-care technologies facilitating decentralized screening. Regulatory and ethical challenges, cost-effectiveness analyses, and standardization hurdles across diverse healthcare settings are also discussed. Finally, we identify research gaps in longitudinal, multi-center validation studies and propose future directions toward precision nephrology, integrating multi-omics data with imaging and wearable sensors to shift CKD management from treatment to prevention. This comprehensive overview informs clinicians and researchers on the translational potential of novel diagnostics in combating the growing CKD burden.